Introducing RDA a guide to the basics after 3R - Oliver, Chris 1951- (Chicago ALA Editions, 2021)
Reflecting the changes to RDA: Resource Description and Access after the completion of the 3R Project, Oliver brings her Special Report up to date. This essential primer provides an overview of the latest developments, focusing on the impact of the 3R Project, the results of aligning RDA with IFLA's Library Reference Model (LRM), and the outcomes of internationalization - c Provided by publisher.
What is RDA? -- RDA : an international standard -- The IFLA bibliographic conceptual models -- RDA's background : evolution from AACR2 into RDA -- RDA : some key aspects -- Using RDA -- RDA after the 3R project.
Includes bibliographical references and index.
Keywords: Descriptive cataloging -- Standards; Cataloging -- Standards